Explaining the asymmetric line profile in Cepheus X-4 with spectral variation across pulse phase. Issue 3 (22nd October 2018) - Bhargava, Yash; Bhalerao, Varun; Ballhausen, Ralf; Fürst, Felix; Pottschmidt, Katja; Tomsick, John A; Wilms, Joern
ABSTRACT: The high mass X-ray binary Cepheus X-4, during its 2014 outburst, showed evidence for an asymmetric cyclotron line in its hard X-ray spectrum. The 2014 spectrum provides one of the clearest cases of an asymmetric line profile among all studied sources with Cyclotron Resonance Scattering Features (CRSF). We present a phase-resolved analysis of NuSTAR and Suzaku data taken at the peak and during the decline phases of this outburst. We find that the pulse-phased resolved spectra are well-fit by a single, symmetric cyclotron feature. The fit parameters vary strongly with pulse phase: most notably the central energy and depth of the cyclotron feature, the slope of the power-law component, and the absorbing column density. We synthesise a 'phase averaged' spectrum using the best-fitting parameters for these individual pulse phases, and find that this combined model spectrum has a similar asymmetry in the cyclotron features as discovered in phase-averaged data. We conclude that the pulse phase resolved analysis with simple symmetric line profiles when combined can explain the asymmetry detected in the phase-averaged data.